Simulation of multi-probe radiofrequency ablation guided by optical surgery navigation system under different active modes. Issue 1 (1st January 2016) - Xu, Leyi; Cai, Ken; Yang, Rongqian; Lin, Qinyong; Yue, Hongwei; Liu, Feng
ABSTRACT: Radiofrequency ablation (RFA) is a crucial alternative treatment for liver cancer with the advantages of minimal invasion and a fast prognosis. However, two problems limit its further application: the orientation of the puncture point and the ablation of large tumors. The optical surgery navigation system in the RFA presents a promising approach for solving the localization problem in the puncturing process, which greatly increases puncture accuracy and has overcome the disadvantages of traditional RFA surgery. In addition, the use of multiple electrodes in the RFA (multi-probe RFA) is proposed and is applied clinically to deal with large tumors. In this study, we present a multi-probe RFA model using the finite element method (FEM) combined with a self-developed optical surgical navigation system. A real 3D liver model was adopted as an effective reference. Based on this model, two-probe RFA simulations were performed under different active modes. An analysis was conducted from the perspective of the temperature and electric potential fields and cell necrosis. The simulation results showed that different active modes had separate advantages and were suitable for different situations. Understanding their advantages can not only help doctors make surgical plans that fit the patients' conditions, but also the understanding can offer a virtual surgery platform for further development in the preoperative planning of RFA incorporated with the surgery navigation system.